Acute pericarditis, Graves' disease, and thymic hyperplasia: a case report. Issue 10 (12th October 2021) - Acquaro, Mauro; Breviario, Federico; Greco, Alessandra; Ghio, Stefano
Abstract: Background: Acute pericarditis as a sign of mediastinal mass is rare and aetiological diagnosis can be challenging without adequate imaging. Case summary: An 18-year-old woman came to our attention describing acute sharp chest pain radiated to the left arm, exacerbated with supine positioning and attenuated while sitting or leaning forward. The electrocardiogram showed diffuse ST elevation and PR depression, with sinus tachycardia. Cardiac biomarkers and D-dimer were negative; echocardiography showed no abnormalities and the absence of pericardial effusion. Her blood work revealed no sign of inflammation or bacterial infection (PCR and procalcitonin were normal); thyroid-stimulating hormone plasma levels were suppressed, showing decompensated thyrotoxicosis. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), Epstein–Barr virus, human immunodeficiency virus, hepatitis C virus, Enterovirus, Parvovirus B19, and Adenovirus tests were normal. Her past medical history was silent, apart from Grave's disease on treatment with methimazole. Chest computed tomography (CT) was performed and showed the presence of slightly increased density pericardial effusion, with a maximum thickness of 15 mm in the upper mediastinum. Finally, cardiac magnetic resonance (MR) identified a mass of 73 × 51 mm located in the upper mediastinum. The mass was subsequently biopsed with video-assisted thoracoscopic surgery and the histological analysis showed thymic hyperplasia. Discussion: This case shows the importance of an adequate clinical suspicion of thymic hyperplasia in the context of acute pericarditis symptoms and known Graves' disease. In this case, a negative chest CT finding may not be sufficient to rule out the diagnosis and cardiac MR imaging is necessary.